PERFORMANS PRODUKSI SAPI BALI PADA POLA PEMELIHARAAN EKSTENSIF DI PULAU BALI - Dwi Dedeh Kurnia Sari; Ricke Marianty; Kristina Kristina (Agrienvi: Jurnal Ilmu Pertanian, 2022)
The purpose of this study was to identify the factors that influence and comparing the production of cattle Bali the maintenance of farming system.This research has been carried in Bangli regency and Jembrana regency. Measurement of Bali cattle production performance was determined several factors, namely Birth Weight (BW), Weaning Weight (WW), Weight Gain (WG), and 1 Year Weight (YW). The research method used was a survey, data were analysis by applying analysis of variance (ANOVA) in Nested Design. The results showed that the production performance (WB, WW, WG, and YW) of Bali cattle with extensive in Bangli regency maintenance was heavier than that of Jembrana regency reared Bali cattle and the average body weight of male Bali cattle was greater than that of female Bali cattle. Based on Birth Weight (BW), weaning weight (WW), weight gain (WG) and Yearling Weight (YW), production performance of Bali cattle is not only influenced by the farming system and sex, but also by feed consumption and the environment.